Peran Rasa Saling Percaya Karyawan dan Dukungan Organisasi dalam Meningkatkan Kebanggaan pada Organisasi di Perusahaan Logistik Malang - Lailatudzurrohmah Lailatudzurrohmah; Nilawati Fiernaningsih (Jurnal Simki Economic, 2025)
This study aims to determine the role of employee mutual trust and organizational support in increasing pride in the organization at the Malang Logistics Company. This study uses a qualitative research method, using seven permanent employees of the Malang Logistics Company as research subjects. Data collection techniques used in this study were observation, interviews, and documentation. The data obtained were analyzed using interactive data analysis from Miles & Huberman. The results of the study indicate that employee mutual trust and organizational support play a role in increasing employee pride in the organization. Both play a role in creating an effective and comfortable work environment so that employees become productive and loyal to the company. The novelty in this study is that the study focuses on mutual trust and organizational support which together can increase pride in the organization.